Policy Perspectives of Dog-Mediated Rabies Control in Resource-Limited Countries: The Ethiopian Situation - Beyene, Tariku Jibat; Mourits, Monique; O'Quin, Jeanette; Leta, Samson; Baruch, Joaquin; Hogeveen, Henk (Frontiers in Veterinary Science, 2020)
One Health disease-control programs are believed to be most effective when implemented within the population transmitting the disease. The World Health Organization (WHO) and partners have targeted the elimination of dog-mediated human rabies by 2030 primarily through mass dog vaccination. Mass vaccination, however, has been constrained by financial resource limitations. The current owner-charged dog vaccination strategy, used in most resource-limited countries like Ethiopia, has not reached the minimum coverage required to build population immunity. Dog vaccination is non-existing in most rural areas of Ethiopia and coverage is less than 20% in urban areas. Although the health and economic benefits of rabies elimination outweigh the costs, the direct beneficiaries (public in general) and those who bear the costs (dog owners) are not necessarily the same. In this perspective paper, we aggregate evidence on the socio-economic burden of rabies in Ethiopia as well as the implications for potential opportunities to control the disease and possibilities to obtain the required funding sources for evidence-based interventions in the control of rabies in Ethiopia.